The role of inter‐individual intolerance in group cohesion and the transition to sociality in spiders. (8th June 2022) - Rose, Clémence; Kyneb, Sarah; Schou, Mads Fristrup; Bechsgaard, Jesper; Bilde, Trine
Abstract: Conspecific tolerance is key for maintaining group cohesion in animals. Understanding shifts from conspecific tolerance to intolerance is therefore important for understanding transitions to sociality. Subsocial species disperse to a solitary lifestyle after a gregarious juvenile phase and display conspecific intolerance as adults as a mechanism to maintain a solitary living. The development of intolerance towards group members is hypothesized to play a role in dispersal decisions in subsocial species. One hypothesis posits that dispersal is triggered by factors such as food competition with the subsequent development of conspecific intolerance, rather than conspecific intolerance developing prior to and potentially driving dispersal. Consistent with this hypothesis, we show that intolerance (inferred by inter‐individual distance) developed post‐dispersal in the subsocial spider Stegodyphus lineatus . The development of conspecific intolerance was delayed when maintaining spiders in groups showing plasticity in this trait, which is advantageous when trade‐offs are not fixed over time. However, major evolutionary transitions, such as the transition to sociality, can permanently modify trade‐offs and cause derived adaptations by the evolution of new or modified traits or evolutionary loss of traits that become redundant. Sociality in spiders has evolved repeatedly from subsocial ancestors, and social life in family groups combined with a lack of interaction with competing groups suggests relaxed selection for the development of conspecific intolerance. In the social Stegodyphus sarasinorum we found no evidence for the development of conspecific intolerance, consistent with the loss of this trait. Instead, we found evidence for conspecific attraction, which is likely to govern group cohesion. Abstract : Intolerance develop post‐dispersal in the subsocial spider Stegodyphus lineatus and the onset is socially context‐dependent.Intolerance is lost in the social spider Stegodyphus sarasinorum and they show conspecific attraction.